Validation of SHOEBOX QuickTest Hearing Loss Screening Tool in Individuals With Cognitive Impairment - Frank, Andrew; Goldlist, Serena; Mark Fraser, Amy E.; Bromwich, Matthew (Frontiers in Digital Health, 2021)
Objectives: The aim of this study was to validate SHOEBOX QuickTest, an iPad-based rapid hearing loss screening tool, in individuals with cognitive impairment. Design: Cross-sectional validation study Setting: Bruyère Research Institute, Ottawa, Canada Subjects and Methods: Twenty-five individuals with mild cognitive impairment (MCI) and mild dementia from the Bruyère Memory Program were included in this study. The study consisted of two components: 1) SHOEBOX QuickTest and 2) Conventional audiometry. Measurements: Pure tone thresholds were measured at frequencies 1000, 2000 and 4000 Hz separately for each ear. 10 dB pure tone threshold ranges were provided by SHOEBOX QuickTest and actual pure tone threshold values were provided by conventional audiometry. Results: 84% of the tested population had matching results between SHOEBOX QuickTest and conventional audiometry. The SHOEBOX QuickTest showed a sensitivity and specificity of 100% and 66.7% respectively. 72% ([95% CI], 60.0%-84.1%) of conventional audiometry thresholds were within the pre-established 10 dB SHOEBOX QuickTest range and 89.33% ([95% CI] (98.34-80.33)) were within +/-5 dB of the 10 dB SHOEBOX QuickTest range. Conclusion: SHOEBOX QuickTest is a valid hearing loss screening tool for individuals with cognitive impairment. Implementing this iPad-based screening tool in memory clinics could not only aid in the timely diagnosis of hearing loss, but also assist physicians in providing a better assessment of cognitive impairment by ruling out hearing loss as a confounding variable.